Gestión del departamento financiero y su efecto en la calidad de atención al usuario en el gad municipal del cantón Buena Fe, periodo 2022-2023 - Alava Zambrano, Evelyn Tatiana (2023)
In this research, the need to evaluate the quality of user service and its relationship with public management in the Municipal GAD of the Buena Fe Canton was raised, with the objective of identifying opportunities for improvement for the Buena Fe community. A bibliographic review was carried out on the concepts of public management and quality of user service, as well as on the tools and strategies that can be implemented to improve the quality of public services. An analysis of the current situation of the public entity was carried out, to fulfill the objectives of the research, which lies in evaluating the quality of care in the financial department and its effect on user satisfaction in the Municipal GAD of the canton. . Good Faith, identifying the level of satisfaction in the provision of services with a research methodology that includes the application of surveys and interviews to users of the public entity, as well as to public servants in charge of customer service. During the interview process, various barriers are identified in the financial department that negatively impact the quality of customer service. The evaluation of responses in the survey carried out among users reflects a clear disagreement with the current physical conditions, highlighting a low level of satisfaction, revealing that the quality of services must be improved, underlining the importance of providing a consistent and precise service, as well as how to understand and respond to user needs.